Kinetic modeling of LDPE pyrolysis using coats-Redfern method - Wong, S. L. (2015)
Pyrolysis of polymer waste can potentially be a source of renewable energy, as it is a possible way to produce liquid fuel. In order to industrialize the process, the kinetic behavior of the pyrolysis has to be well understood. In this study, pyrolysis of virgin low density polyethylene (LDPE) was studied using thermogravimetric analysis (TGA). The test was carried out from 303-923 K at 20K/min in a nitrogen atmosphere. The TGA result was used to develop suitable models to calculate the activation energy, E, and pre-exponential factor, A, using Coats-Redfern method. Proximate and elemental analysis was also carried out on the LDPE sample. It was discovered that all reaction models were able to produce satisfactory linear fit of the data, with high correlation coefficients. Therefore, Coats-Redfern method cannot be used alone, but must be coupled with other methods to determine the correct reaction mechanism for the pyrolysis. By assuming first-order reaction, the calculated activation energy and pre-exponential factor are 166.75 kJ/mol and 4.97 x 1011 s-1, respectively.